SEVER ACUTE PANCREATITIS: ASSESSMENT OF CLINICAL CHARACTERISTICS, IMAGING DATA, ACCOMPANYING PATHOLOGY, COMPLICATIONS AND CONSEQUENCES - Tetiana V. Formanchuk; Mariya I. Pokidko; Maksym A. Hudz; Vitaliy А. Katsal; Andrii A. Zhmur (Клінічна та профілактична медицина)
Introduction. The issue of early stratification of patients with acute pancreatitis (AP) by severity is crucial in order to start infusion therapy in time and reduce the mortality rate.